Unraveling the genomic reorganization of polygalacturonase-inhibiting proteins in chickpea - Ellur, Vishnutej; Wei, Wei; Ghogare‬, Rishikesh; Solanki, Shyam; Vandemark, George; Brueggeman, Robert; Chen, Weidong (Frontiers in Genetics, 2023)
Polygalacturonase inhibiting proteins (PGIPs) are cell wall-anchored proteins that inhibit pathogen polygalacturonases (PGs). PGIPs, like other resistance genes, contain extracytoplasmic leucine-rich repeats (eLRRs), which are required for pathogen PG recognition. The importance of these PGIPs in plant defense has been well documented. This study focuses on chickpea (Cicer arietinum) PGIPs (CaPGIPs) owing to limited information available on this important crop. In this study, we identified and characterized two novel Capgips (Capgip3 and Capgip4) in addition to the previously reported Capgip1 and Capgip2. Our analysis showed that CaPGIP1, CaPGIP3, and CaPGIP4 proteins contain N-terminal signal peptides, ten LRRs, theoretical molecular mass, and isoelectric points like other legume PGIPs. However, the previously reported CaPGIP2 cannot be classified as a true PGIP since it lacked a signal peptide, more than half of the LRRs, and other characteristics of a typical PGIP. Phylogenetic analysis and multiple sequence alignment revealed that the Capgip amino acid sequences are similar to the other reported legumes. Several cis-acting elements that are typical of pathogen response, tissue-specific activity, hormone response, and abiotic stress-related are present in the promoters of Capgip1, Capgip3, and Capgip4. Localization experiments showed that Capgip1, Capgip3, and Capgip4 are located in the cell wall or membrane, whereas Capgip2 is found in the endoplasmic reticulum. Capgip transcript levels analyzed at normal conditions show constitutive tissue specific expression and heterozygous expression patterns analogous to other defense related gene families. All these findings suggest that CaPGIPs could have the potential to combat chickpea pathogens.